Biology and morphomatrics of lemon butterfly Papilio demoleus (Lepidoptera: Papilionidae) on bael, Aegle marmelos in Arid Region of Rajasthan (Indian Journal of Arid Horticulture, 2025)
Biology and morphometrics studies of the lemon butterfly, Papilio demoleus L., were carried out on bael, Aegle marmelos. Eggs were laid singly on the under surface of tender leaves and on tender twigs. The pooled mean duration of the different stages of the lemon butterfly was as follows: the incubation period was 2.80 days, the larval period was 9.23 days, the pre-pupal period was 0.99 days, the pupal period was 8.11 days, the female adult longevity period was 6.95 days, and the male longevity period was 3.85 days. The average length, width, and wing expanse of the male butterfly were found to be 27.96 mm, 5.99 mm, and 88.51 mm, respectively. The female butterfly was found to be 29.05 mm in length, 6.32 mm in width, and had a wing expanse of 91.07 mm, respectively. The morphometric variations of different life stages of the citrus butterfly have been recorded.
Keywords: Papilio demoleus; Aegle marmelos; Biology; Morphometrics